MONEY LAUNDERING DAN KETERLIBATAN WANITA (ARTIS): TANTANGAN BARU BAGI AUDITOR INVESTIGATIF - Rhety Ayu Dewayani; Anis Chariri (Diponegoro Journal of Accounting, 2015)
This study aims to discuss new mode of Money Laundering in Indonesia. The focus of this study is to reveal cases of Money Laundering involving female artist.This study used descriptive analytical on the results of interview with the informant. The analyzed data in this study is the results of interview with government auditors in BPK representative offices in Central Java and Central Java BPKP. The data is obtained through direct interviews.The results of this study showed that government auditors was acknowledge the essence of Money Laundering according with the regulations and expert opinion. There is some dissimilarity opinion from the informant about the new mode of Money Laundering. Some argue that the female artist merely a victims, the other argue that they are involved as corruption fund’s holders.